A Study on The Performance Appraisal Method of Vocational Education Teachers Using Promethee II - Handaru Jati (JOURNAL OF EDUCATION, 2012)
Evaluating vocational education teachers' performance is an important link of teaching  management and an important guarantee of improving teaching quality. In conducting teaching, research and community service, vocational education teachers should weight more on quality than quantity. In this context, individual habit reacts to the demanded jobs which are influenced by his/her knowledge; attitude, and skill. The aim of this study is to develop the vocational education teachers' performance quantitative appraisal and determine the evaluation index based on academic performance. Criteria for performance are: teaching load, publication, research, conferencing, consultancy, services, teaching attitude, teaching content, teaching method, and teaching  effect.  The Analytic  Hierarchy  Process (AHP)  and  PROMETHEE (Preference Ranking  Organisation METHod for Enrichment Evaluations) II analyses were used in the performance  appraisal. The findings show that the MCDM  approach is a viable tool in solving the teacher  selection decision problems. It allows the decision maker to rank the candidate alternatives more efficiently and easily.   Keywords: performance,   appraisal  method, vocational education teacher, analytic hierarchy process, PROMETHEE II